EPR and dielectric spectroscopy of reorienting Cr³⁺-Li⁺ pair centres in Li₂Ge₇O₁₅ crystal - Volnianskii, M.D.; Trubitsyn, M.P.; Obaidat, Yahia A.H. (Condensed Matter Physics, 2007)
Earlier it has been shown that in the lithium heptagermanate Li₂Ge₇O₁₅ structure the chromium doping ions substitute the germanium hosts and create Cr³⁺-Li⁺ pair centres. In the paper EPR and dielectric spectra of Li₂Ge₇O₁₅:Cr³⁺ crystal are studied in the temperature range 300 ÷ 500 K. The thermally activated reorientation of Cr³⁺-Li⁺ pairs has been detected through EPR line width broadening and dielectric relaxation.